2013
DOI: 10.1186/1471-2431-13-119
|View full text |Cite
|
Sign up to set email alerts
|

Screening for developmental delay among children attending a rural community welfare clinic in Ghana

Abstract: BackgroundPeriodic screening for developmental delays (DD) could avert the incidence of disability among children. However, such routine programme is yet to take off in rural welfare clinics in Ghana.MethodMothers of under-5 children who were attending rural child welfare clinic participated in this study. The socio-demographic data of the mothers and their children were recorded. The children were screened to assess their gross motor skills, fine motor skills, communication skills, problem solving/cognition a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
52
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 25 publications
7
52
3
Order By: Relevance
“…factor analysis, item analysis, etc.) . Two studies reported on the ASQ's relation to other measures via correlations with a criterion measure .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…factor analysis, item analysis, etc.) . Two studies reported on the ASQ's relation to other measures via correlations with a criterion measure .…”
Section: Resultsmentioning
confidence: 99%
“…factor analysis, item analysis, etc.). 33,[46][47][48][49][50][51][52][53][54][55][56][57][58] Two studies reported on the ASQ's relation to other measures via correlations with a criterion measure. 49,50 Finally, six studies reported on the consequences of ASQ use.…”
Section: Psychometric Studiesmentioning
confidence: 99%
“…The initial search results generated a large volume of studies and reviews related to developmental screening processes and instruments. Search results yielded guidelines and recommendations for the use of screening tools to identify children with DD or ASD (e.g., American Academy of Pediatrics, 2006;Charman & Gotham, 2013;King et al, 2010) and reports of screening tools used in different populations (e.g., Barton et al, 2012;Bello, Quartey, & Appiah, 2013;Grossman et al, 2010;Perera, Wijewardena, & Aluthwelage, 2009). The search results included a large number of studies that described tool development and validation (e.g., Allen, Silove, Williams, & Hutchins, 2007;Bhave, Bhargava, & Kumar, 2010;Durkin et al, 1994Durkin et al, , 1995 or adaptation of screening tools (e.g., Gladstone et al, 2008;Kakooza-Mwesige et al, 2014;Soto et al, 2015), as well as comparisons between screening tools (e.g., Mayes et al, 2009;Murray, Mayes, & Smith, 2011;Snow & Lecavalier, 2008).…”
Section: Search Strategymentioning
confidence: 99%
“…Factors associated with gross motor delay among typically developing children aged 0-5 years include in part, child characteristics (e.g. low birthweight 11 and prematurity 11,15,16 ) and family characteristics (e.g. low parental education 11,16 and low familial socio-economic status 11,12 ).…”
mentioning
confidence: 99%
“…low birthweight 11 and prematurity 11,15,16 ) and family characteristics (e.g. low parental education 11,16 and low familial socio-economic status 11,12 ). One of the publications resulting from the Australian Early Development Census data examined socio-demographic factors associated with the physical health and wellbeing domain in the Northern Territory.…”
mentioning
confidence: 99%